A note on the computation of the equity premium and the market value of firm equity - Burkhard Heer; Alfred Maußner (Center for Economic Studies and ifo Institute (CESifo), 2010)
Turnovsky (1995) derives in a continuous-time model of a decentralized economy that the correct specification of the firm's objective function is to maximize the initial value of its outstanding securities. The firm value is the discounted flow of real earnings. For the discrete-time version of the model, we show that the correct computation of the firm value needs to be modified. Depending on the specific formula employed, different values of the equity premium result.
Keywords: G12; C63; E22; E32; 330; asset prices; firm value; equity premium; Unternehmensbewertung; Risikoprämie; Betriebsvermögen; Einnahmen; Discounted Cash Flow; Theorie